Unusual Intestinal Involvement by Paracoccidioidomycosis Diagnosed After Oral Manifestation - Neves-Silva, Rodrigo; Fernandes, Patrícia Maria; Santos-Silva, Alan Roger; Vargas, Pablo Agustin; de Souza Cavalcante, Ricardo [UNESP]; Lopes, Marcio Ajudarte (Springer Nature, 2018)
Paracoccidioidomycosis is a common deep fungus infection in South America, particularly in Brazil. It is acquired through inhalation and primary involvement of lungs. Subsequently, dissemination may occur and oral mucosa is frequently affected and actually, in most of the cases the diagnosis is established because of the oral lesions. Thus, the role of the dentist is fundamental to correct diagnosis. However, the involvement of intestine is rarely reported. The current case describes a 36-year-old man who presented abdominal pain and intestinal constipation, being suspected and then confirmed as paracoccidioidomycosis after already be diagnosed with this disease by a dentist through oral manifestations.
Keywords: Diagnosis; Intestine; Oral cavity; Paracoccidioidomycosis